ANALISIS PENYEBAB PENGUCAPAN KATA TOXIC DI KALANGAN MAHASISWA - Andi Saadillah; Nanda Saputra; Muh. Alwi Suhajardita (Program Studi Pendidikan Bahasa dan Sastra Indonesia, FKIP, Universitas Halu Oleo Kampus Bumi Tridharma Andounohu Kendari, Provinsi Sulawesi Tenggara – Indonesia, 2023)
students to have bad morals, that is, they often say dirty and dirty words or what are commonly called toxic words. This is very unfortunate, The purpose of this research is to analyze the causes of students' pronunciation saying toxic. This research is a qualitative research by analyzing students of the Indonesian Language Education Study Program, Faculty of Teacher Training and Education, Nineteen November University, Kolaka. This research focuses on male students of PBI Study Program class of 2022. Data collection was carried out on campus and boarding houses using data collection techniques in the form of observation or direct observation, recording and interviews. Interview techniques were used to find data on the causes of toxic word pronunciation among students. The results of the study showed several toxic vocabularies, namely: freak, jerk, bastard, damn, idiot, and stupid. The causes for pronouncing the word toxic include: anger, happiness, confusion, unhealthy associations, and mindset. Keywords: Toxic, Student